Movimento dos Trabalhadores Rurais sem Terra e o Instituto Educar: a resistência da educação do campo sob o prisma das teorizações e políticas educacionais - Stefanello, Flávia (2022)
The research approach the understanding of the path that constitutes the Education of the Field from the perspective of the Landless Rural Workers Movement (MST) and the educational policies that are part of this context, having as locus the Educar Institute, in Pontão-RS. As a theoretical basis, the reference that guides the thesis is Antonio Gramsci, starting from the main concepts exploited by the author and that help in understanding social struggles, such as the struggle for land, land reform and education. Also make this stage, Karl Marx's theorizations that support Gramscian theory. The research purpose is the formative process that occurs especially at the Educar Institute, a countryside school located in the Nossa Senhora Aparecida Settlement. For this purpose, the research problem focuses on the following question: How do the theorizations and educational policies that constitute the educational processes in the MST, especially in the Educar Institute? The structure of this research begins with the resumption of some concepts exploited by Gramsci (1976; 1982; 1987; 1988; 1995; 1999; 2001; 2002; 2007) and which are visibly present in social struggles. Following, the main events related to field Education and its intimate connection with the MST, specifically at the Educar Institute. The main educational policies aimed to this segment are as well debated and analyzed in the context of Countryside Education. At last, from a field study at the Educar Institute, the thesis has a hermeneutic analysis of the mental perceptions provided by the educator and militant, Salete Campigotto, which points elements that converge each other with the concepts theorized by Gramsci and Marx, as well as dialogue with other thinkers, such as Freire, Makarenko, Pistrak and Krupskaya. Also comprises this round, the relationship of these elements with the current educational policies of the countryside and their current dissemble. As a result of the research, the fruitful relationship between Marxist and Gramscian concepts, associated with Soviet socialist pedagogy, indicating the moments in which they interweave with educational policies for Countryside Education. Thus, such policies, through programs such as PRONERA, become elements of resistance in the MST, because in educating institutions, such as the Educar Institute, give subsidies for the continuity of the educational process forcing the protagonism of the collective subjects of the countryside, substantially in the context of land reform. It is a qualitative, exploratory, bibliographic and documental research anchored by a field study.